Microsurgical simulation, a 'cheep' solution. Issue 10 (December 2020) - Jenkinson, Andrew; Kittur, Madhav A.; Shah, Ketan
Abstract: There is a demand for simulation-themed courses within maxillofacial surgery, yet these are often expensive. With this in mind, we used a non-living chicken thigh model to simulate microsurgical procedures on a training day for specialty registrars. The advantages and limitations of the simulation were explored through participant feedback. This model was found to be a useful, cost-effective simulation which was valued by trainees within our specialty.